Analysis of the Effectiveness of Leaders Based on Gender in Islamic-Based Non-Profit Organizations - Nadya Ayu Saraswati; Ahyar Yuniawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The role of women in top management positions in companies or organizations is still less than the role of men, while in general the female population is higher than the male population. This phenomenon indicates that there is a problem in the role of women in occupying top management positions. The view of patriarchal culture in Indonesia and the inappropriate interpretation of the Qur'an cause limitations on the role of women outside the home, especially as leaders and increase discrimination against women. This study discusses the differences in perceptions of male and female leaders and the application of Islamic leadership in non-profit Islamic organizations. The research was conducted using a mix method that integrates quantitative and qualitative research at an Islamic educational institution in the city of Semarang. The conclusion of this study is that male leaders are perceived to have higher effectiveness than female leaders. Male leaders listen more effectively to subordinates and share tasks more fairly than female leaders. Leaders in educational institutions that are the object of research have also behaved in accordance with the five behaviors of Islamic leaders. As a result, the management of the company or organization can choose leaders according to the direction and needs of the organization.